Recaudación tributaria y ejecución presupuestaria en la Municipalidad Provincial de Loreto Nauta 2024 - Coriat Zavaleta, Christian Gerard (2025)
The objective of this research work was to determine to what extent tax collection and budget execution are related in the Provincial Municipality of Loreto Nauta 2024. The study is of a basic type, with a quantitative approach with a non-experimental cross-sectional design. The sample consisted of 100 people. In this study, the survey and the questionnaire were used as instruments. In the results it could be observed that, out of a total of 25 respondents in Tax Collection and Budget Execution in the Provincial Municipality of Loreto Nauta 2024, 1.5% responded that they never collect taxes in the Provincial Municipality of Loreto Nauta 2024, therefore, 5.7% commented that almost never, in addition 11.4% stated that sometimes, on the other hand, 35.7% expressed that almost always, meanwhile, 45.7% stated that they always collect taxes in the Provincial Municipality of Loreto Nauta 2024. Concluding that tax collection is directly related to budget execution in the Provincial Municipality of Loreto Nauta 2024, efficient management of tax collection allows greater availability of financial resources, which positively impacts the planning and execution of the municipal budget. On the contrary, low tax collection can limit investment in infrastructure, social programs and other essential services for the community.